Obtaining biological silage from lactic fermentation of fish waste (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
Fish waste, when used as raw material, is considered a valuable byproduct due to its nutrient content, and through transformation processes, it can help prevent environmental pollution. The waste generated from fishing activities is not adequately treated in terms of its final disposal, which contributes to environmental contamination. Additionally, these waste materials are not used rationally due to a lack of knowledge regarding the applicable technological processes for utilizing the byproducts generated on a daily basis. This study aims to characterize and utilize these agro-industrial waste materials in the production of biological silage. The objective of this research was to obtain biological silage using fish waste in Gamarra (Cesar). An experimental factorial design of 2 x 3 was employed, with the first factor being the carbon source (molasses) at two levels of 12% and 18%, and the second factor being the fermenting agent, which utilized yogurt at three levels of 6%, 11%, and 15%. These factors were evaluated at a confidence level of 95% (P
Keywords: Aquaculture; Biotechnology; Nutrition; Fish.